2002
DOI: 10.1001/archsurg.137.5.590
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Mediators and Organ Function in Patients Undergoing Planned Relaparotomy vs Conventional Surgical Therapy in Severe Secondary Peritonitis

Abstract: Hypothesis: Planned relaparotomy (PRL) has been suggested to have detrimental effects on the systemic activation of inflammation mediators, thereby enhancing organ dysfunctions as assessed by clinical scores in secondary peritonitis.Design: Prospective, nonrandomized control trial.Setting: Intensive care units of an urban and a university teaching hospital.Patients: Twenty-nine patients with secondary peritonitis.Interventions: Of the 29 patients with comparable initial peritonitis conditions, 11 underwent PRL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 61 publications
1
9
0
1
Order By: Relevance
“…19 This proinflammatory cytokine response is linked to the upregulation of coagulation factors, adhesion molecules, and opsonic components. 20 These findings are consistent with reports from animal studies. Mice who survived an episode of peritonitis had significantly decreased levels of TNF␣ and IL-6 in blood as well as in the peritoneal cavity, 21 and TNF-deficient mice exhibit significantly improved morbidity and mortality from "multiple organ dysfunction syndrome" induced by the administration of zymosan.…”
Section: Discussionsupporting
confidence: 91%
“…19 This proinflammatory cytokine response is linked to the upregulation of coagulation factors, adhesion molecules, and opsonic components. 20 These findings are consistent with reports from animal studies. Mice who survived an episode of peritonitis had significantly decreased levels of TNF␣ and IL-6 in blood as well as in the peritoneal cavity, 21 and TNF-deficient mice exhibit significantly improved morbidity and mortality from "multiple organ dysfunction syndrome" induced by the administration of zymosan.…”
Section: Discussionsupporting
confidence: 91%
“…25,26 We also observed that patients treated with the planned strategy had longer ICU stays and had a longer overall hospital stay. The duration of mechanical ventilation was significantly longer for the planned treatment patients.…”
Section: Commentmentioning
confidence: 76%
“…[2][3][4] However, repeated or even unnecessary surgical procedures are an additional risk factor for the patient and may further enhance morbidity. [5][6][7] Facing this clinical dilemma, there is major interest in the search for an optimum diagnostic tool for an early, noninvasive, and reliable diagnosis of abdominal infections and sepsis. 8 Clinical scoring systems allow satisfactory prediction of overall prognosis [9][10][11][12][13][14] and are an established means of interinstitutional comparison of patient groups for study purposes.…”
mentioning
confidence: 99%